Competitiveness and symbiotic efficiency in alfalfa of Rhizobium favelukesii ORY1 strain in which homologous genes of peptidases HrrP and SapA that negatively affect symbiosis were identified - Berais-Rubio, Andrés; Morel Revetria, María A.; Giménez, Matías; Signorelli, Santiago; Monza, Jorge (Frontiers in Agronomy, 2023)
In acid soils, Rhizobium favelukesii strains, known as Oregon-like strains, are a potential risk for alfalfa production given their parasitic behaviour. In this study, we isolated five parasitic strains (ORY1 to ORY5) from alfalfa nodules grown in Uruguayan acid soils, with a 99.7% and a 100% 16S rRNA gene sequence identity to R. favelukesii type strain of LUP83. The BOX profiles of the five isolates showed two different patterns, suggesting some diversity among these acid-tolerant isolates. The genome sequence analysis of R. favelukesii strains ORY1, LPU83, and Or191 showed that they have around 87.5% of common coding genes, including the symbiotic genes. Moreover, the phylogenetic analysis of ORY1 symbiotic genes nifH, nifD, nifK, nodA, nodB, and nodD were related to the symbiotic genes of E. meli-loti. We teste ORY1 competitiveness by inoculating seeds with 99:1 and 1:99 ratios of ORY1::gusA/ E. meliloti U143. In both treatments, ORY1::gusA occupied more than 50% of nodules, evidencing its high competitiveness. However, the aerial biomass in these treatments was remarkably different, suggesting that the nodules induced by the efficient strain are es-sential to provide enough N for optimal plant growth. These findings support the needing of inoculating in areas where inefficient strains are likely to be present. Finally, we found three genes that encode amino acid sequences for domains of M16 peptidases (with homology to bacterial hrrP and sapA genes), two of them were contiguous and located in an accessory plasmid, whereas the other one was a chromosomal gene. These genes are likely to be in-volved in the parasitic behaviour of ORY1 strain.